Design for shared driverless vehicles of the future - Wu, Jiayu; Clark, Sheila; Kennard, Ashley; Hesseldahl, Katrine Dalum; Diels, Cyriel (The Design journal, 2025)
On-demand shared transportation is a major new mobility innovation and potentially the main mode of transport in coming decades. Studies show that driverless vehicles have potential to accelerate uptake of shared vehicles at scale. People perceive sharing positively but do not necessarily translate perception into action, with desire for personal space a major reason for unwillingness to share vehicles. Design research is a powerful tool when creating methods and processes to anticipate future possibilities by visualising detailed features of proposed products. We present a set of design research methods engaging end users in a variety of empathy activities and a design process to translate their needs into visual concepts for future shared driverless vehicles that are attractive and more likely to be adopted.